Sử dụng hồi qui đồng tích hợp để xử lý vấn đề nghiệm đơn vị trong nghiên cứu xác định hàm cầu nhập khẩu urê của Việt Nam. - Nguyễn, Thế Hòa (Trường Đại học Thủy Lợi, 2020)
Determining a demand function or a import demand function is one of the basic and meaningful studies in economics, since it may be used for many economic purposes such as forecasting quantity demanded for following time periods, assessment of effects of government policies on social welfair changes, especially taxation, and others. To do so, one must use multiple regression analysis in econometrics. In this process one has to cope with the unit root problem. But much of time series have unit roots (nonstationary series). That means it can lead spurious results and a relationship between the variables of the model in fact none exists. With traditional approach of Johansen method, one has to difference a variable before using it in a regression. But it is required much more data and differencing may result in a loss of information and some basic economic laws distorted; and it also makes other difficulties for the reseachers. According to R.F Engle và C.W.J. Granger, if two time series have unit roots but their linear conbination will be stationary, so they are co-integrated. That means, we can use two nonstationary series with original levels to find out that they may have a long-run equilibrium relationship. With this ideal, I had using co-integrating regression to deal with the unit-root problem in the research of forecasting Import Demand for ure of Viet Nam. This study confirms to exist really a long-run equilibrium relationship between the import demand of ure (the dependent variable) and the real price of ure, the total food production output, the domestic ure supply, the total cultivated area (explained variables) of Viet Nam in the process of innovation, which is reported here.